Penolakan Penyediaan Alat Kontrasepsi Bagi Anak Dalam Perspektif Teori Perlindungan Anak oleh Arif Gosita - Anjani, Putri Ageng; Setyorini, Erny Herlin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Children are the next generation of a nation, it is not surprising that the state must guarantee child protection in order to achieve child welfare. However, the state is often faced with the phenomenon of problems related to child protection, namely free sex by children. As a form of child protection, the state ensures that children also need reproductive health efforts. This is stated in Government Regulation Number 28 of 2024 concerning implementing regulations for Health Law Number 17 of 2023, that the provision of contraceptives is one part of reproductive health efforts for children. This study will analyze the provision of contraceptives for children from the perspective of Arif Gosita's child protection theory, which in this theory can be understood that explaining good child protection must be based on Pancasila as a way of life and the nation's moral ideals. The type of research used in this study is normative legal research, namely a method that analyzes the relationship and alignment between legal principles, legal norms, and scholarly opinions (theories) and other rules related to the main problem to be discussed to answer the legal issues faced.